Elucidating the Structural Evolution of a Highly Porous Responsive Metal-Organic Framework (DUT-49(M)) upon Guest Desorption by Time-Resolved in Situ Powder X-ray Diffraction - Garai, Bikash; Bon, Volodymyr; Walenszus, Francesco; Khadiev, Azat; Novikov, Dmitri; Kaskel, Stefan (Crystal Growth and Design, 2021)
Removal of the guest molecules from the pores of metal-organic frameworks (MOFs) is one of the critical steps in particular for highly porous frameworks associated with high internal stress. In the case of isostructural mesoporous DUT-49(M) (M = Cu, Ni, Mn, Fe, Co, Zn, Cd) frameworks, only DUT-49(Cu) and DUT-49(Ni) could be successfully desolvated so far and only by using supercritical activation. To get a deeper insight into the processes occurring upon the desorption of the solvent from the pores of DUT-49(M), the desolvation was monitored in situ by synchrotron powder X-ray diffraction (PXRD). Analysis of the time-resolved PXRD data shows the full structural transformation pathway of the solid, which involves continuous and discontinuous phase transitions from the open pore (op) to the intermediate pore (ip) phase and from the ip to the contracted pore (cp) phase for DUT-49(Cu) and DUT-49(Ni). For DUT-49(Zn), the op to ip transition is directly followed by amorphization of the framework. All other frameworks show direct amorphization of the op phase.
CRIS-Team Scopus Importer:2022-04-14